Harmony of Worship and Empowerment : The Role of The Sabilillah Mosque For The Health of The Ummah - Keyla Sinta Bella; Keysha Mikeyla Alista; Arvyansyah Rizquna; Pradizca Aprillio Nur Fahrezi (Noor: Journal of Islamic Studies, 2026)
This study examines the role of Masjid Sabilillah Malang as a religious center and a hub for community health empowerment within the framework of modern Islamic civilization. The research focuses on how the mosque integrates Islamic values with sustainable promotive, preventive, and curative health programs. Using a qualitative approach with a case study design, data were collected through in-depth interviews, observations, and documentation involving mosque administrators, LAZIS Sabilillah, and Sabilillah Medical Service (SMS). The findings reveal that Masjid Sabilillah has implemented various health initiatives, including mass circumcision, free medical check-ups, health counseling, cardiac exercise programs, and community ambulance services. Institutional collaboration with health centers, medical professionals, and social organizations significantly supports program sustainability. These initiatives contribute to increased health awareness, strengthened social solidarity, and reduced financial burdens among low-income communities. However, challenges remain, particularly related to limited public awareness of health as an integral part of worship. This study concludes that Masjid Sabilillah demonstrates strong potential as a national model of a “Healthy Mosque” that integrates spiritual, social, and health dimensions to promote holistic community development.